Serum D-Dimer Concentrations are Increased after Pediatric Traumatic Brain Injury - Berger, Rachel P. (J Pediatr, 2014)
OBJECTIVE: To determine whether d-dimer would be increased in children with traumatic brain injury (TBI), specifically mild abusive head trauma (AHT). STUDY DESIGN: D-dimer was measured using multiplex bead technology in 195 children <4 years old (n=93 controls without TBI, n=102 cases with TBI) using previously collected serum. D-dimer was then measured prospectively in a clinical setting in 44 children (n=24 controls, n=20 cases). Receiver operator curves (ROC) were generated for prospective data. RESULTS: In both the retrospective and prospective cohorts, median (25(th)–75(th) percentile) d-dimer was significantly higher in cases vs. controls. An ROC demonstrated an area under the curve (AUC) of 0.91 (95% CI: 0.83 – 0.99) in the prospective cohort. At a cut-off of 0.59μg/L, the sensitivity and specificity for identification of a case was 90% and 75%, respectively. CONCLUSIONS: Our data suggest that serum d-dimer may be able to be used to identify which young children at risk for AHT might benefit from a head computer tomography or other additional evaluation. Additional data are needed in order to better identify the clinical scenarios which may result in false positive or false negative d-dimer concentrations.